Prognostic Role and Diagnostic Power of Seven Indicators in COVID-19 Patients - Ding, Lili; Zhang, Wanwan; Zhang, Fengling; Huang, Chaoqun; Yang, Ming; Tang, Zhouping; Li, Yongwu; Mi, Jun; Zhong, Weimin (Frontiers in Medicine, 2021)
Prognostic role and diagnostic ability of COVID-19 disease indicators are not clearly elucidated. The aim of the current study was to investigate prognostic role and diagnostic ability of several COVID-19 disease indicators including levels of oxygen saturation, leukocytes, lymphocytes, albumin, C-reactive protein (CRP), interleukin-6 (IL-6) and D-dimer in COVID-19 patients. Level of oxygen saturation, lymphocytes and albumin were significantly higher in common and severe clinical type patients compared with those in critical type patients. However, levels of leukocytes, CRP, IL-6 and D-dimer were significantly lower in common and severe type patients compared with those in critical type patients (P < 0.001). Moreover, the current study demonstrated that the seven indicators have a good diagnostic powers in COVID-19 patients Furthermore, a two-indicator (CRP and D-dimer) prognostic signature in training and testing datasets was constructed and validated to better understand the prognostic role of the indicators in COVID-19 patients. Patients were classified into high-risk and low-risk groups based on median-risk score. Findings of Kaplan-Meier curve analysis indicated significant divergence between high-risk and low-risk groups. Findings of receiver operating curve (ROC) analysis indicated good performance of the signature in prognosis prediction of COVID-19. In addition, a nomogram was constructed to assist clinicians in developing clinical decision-making for COVID-19 patients. In conclusion, findings of the current study demonstrated that the seven indicators are potential diagnostic markers for COVID-19 and a two-indicator prognostic signature identification may improve clinical management for COVID-19 patients.